تقويم كفاءات متعلمي التربية البدنية والرياضية في ظل البرنامج الدراسي المقرر - رواب, عمار; معتز بالله, شريف (دفـاتر المـــــــــــخبـر; No 19 (2018): مجلة دفاتر, 2018)
هدفت هذه الدراسة إلى " تقويم كفاءات متعلمي التربية البدنية والرياضية في ظل البرنامج الدراسي المقرر " لدى متعلمي السنة الرابعة متوسط في بلدية بسكرة بالجزائر، حيث تم استخدام المنهج الوصفي نظرا لملائمته وطبيعة الدراسة وعينة مقصودة مكونة من 164 متعلم (90 متعلم من الإناث و 74 متعلم من الذكور). واخترنا وضعية ادماجية منتقاة من منهاج المادة كأداة لجمع البيانات لتقويم الكفاءات بعد المرور بالبرنامج الدراسي المقرر من خلال القيام بالاختبار القبلي والاختبار البعدي  وقد أسفرت نتائج هذه الدراسة على عدم وجود أثر لبرنامج التربية البدنية والرياضية المقرر للسنة الرابعة متوسط على كفاءات المتعلمين ذكور وإناث. الكلمات المفتاحية : تقويم الكفاءات، البرنامج الدراسي المقرر. This study aimed to evaluate the learner’s competencies of physical and sport education on the light of syllabus in the learners of fourth year middle school at Biskra municipality at Alegria where the descriptive method sample which consist of 164 learners ( 90 males and 74 females). Fur he rmore ,we have chose nintegrated situation picked from the syllabus of the subject as a tool in order to gather the data to evaluate the competencies after going through the course by doing the pre-test and post-test The result shows that physical and sport education syllabus of fourth year middle school has no impact on the competencies of both learners male and female . Key Word : Evaluation of the learner’s competencies   / syllabus